Review on secured data capabilities of cryptography, steganography, and watermarking domain - Farah Qasim Ahmed Al-Yousuf; Roshidi Din (Institute of Advanced Engineering and Science, 2020)
Due to the increment of using Internet to transfer the critical and secret data, many studies interested in secured data and investigated many ways to secure the transferred information. This paper presents a review study on the field that used in a secured data domain. The main objective of this study is explore the capabilities of secured data that used widely by researchers. Furthermore, the benefits and the drawbacks for each of secured data domain are also studied. This paper concludes that cryptography techniques could be utilized with steganography and watermarking in secured data domain to enhance the security mechanisms.